PENGELOLAAN PARIWISATA BERKELANJUTAN STUDI KASUS:DESA WISATA BLUE LAGOON DI KABUPATEN SLEMAN, DIY - Meitolo Hulu (Journal of Tourism and Economic, 2018)
The development of tourism has experienced significant growth in the past decade. The growth of new tourist destinations in Indonesia adds to the diversity of destinations for tourist visits. A tourist village that highlights the uniqueness and distinctiveness of a village, one of the tourist destinations that is crowded with tourists today. The purpose of this study is to find out the attractiveness of tourists towards the sustainability of tourist villages Blue Lagoon. This study fully uses descriptive qualitative methods. Data collection is done by interviewing managers and visitors who are considered to be able to provide information about the availability of facilities, management of the tourist village of Blue Lagoon. The researcher also conducted direct observations in the field for one month, as well as collecting secondary data from related theoretical sources. Data collected, then interpreted according to the authenticity of the data obtained. The results of this study indicate that the tourist village of Blue Lagoon is visited by tourists because of the very natural environmental conditions and adequate facilities so that in the future managers pay more attention to the carrying capacity of the environment for sustainability.Keywords: Nature Tourism, Tourism Village, Environmental Conditions, Tourism Sustainability.